2019
DOI: 10.1038/s41563-019-0503-4
|View full text |Cite
|
Sign up to set email alerts
|

Furin-mediated intracellular self-assembly of olsalazine nanoparticles for enhanced magnetic resonance imaging and tumour therapy

Abstract: One strategy to enhance tumor retention of imaging agents or anti-cancer drugs is rational design of probes that undergo a tumor-specific enzymatic reaction which prevents them from being pumped out of the cell. Here, the anticancer agent olsalazine (Olsa) was conjugated to the cellpenetrating peptide RVRR. Taking advantage of a biologically compatible condensation reaction, Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
156
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(157 citation statements)
references
References 59 publications
1
156
0
Order By: Relevance
“…[170][171][172] Some studies even demonstrated that the successful accumulation of nanomedicine in the solid tumor after systemic administration could be less than 1% of the injected dose, which will significantly affect nanomedicine efficacy. [173] Though in early studies, pretreatment by many drugs may block RES or MPS and augment tumor accumulation, the inherent toxicity and immunosuppressive effects of these drugs have limited their further clinical use. [174][175][176][177] Therefore, initially evading vascular clearance will directly improve nanomedicine efficacy in cancer therapy.…”
Section: Redesigning the Physicochemical Parameters Of Ahcns To Overcmentioning
confidence: 99%
See 1 more Smart Citation
“…[170][171][172] Some studies even demonstrated that the successful accumulation of nanomedicine in the solid tumor after systemic administration could be less than 1% of the injected dose, which will significantly affect nanomedicine efficacy. [173] Though in early studies, pretreatment by many drugs may block RES or MPS and augment tumor accumulation, the inherent toxicity and immunosuppressive effects of these drugs have limited their further clinical use. [174][175][176][177] Therefore, initially evading vascular clearance will directly improve nanomedicine efficacy in cancer therapy.…”
Section: Redesigning the Physicochemical Parameters Of Ahcns To Overcmentioning
confidence: 99%
“…To effectively target and enrich antitumor drugs, achieve deep intracellular infiltration, and prolong the retention of nanodrugs, Yuan et al designed a small reactive molecule composed of furin enzyme substrates (RVRR), olsalazine (Olsa), and 2-cyano benzothiazole (CBT) (Figure 9a). [173] When the small reactive molecule (Olsa-RVRR) infiltrated into cancer cells with high expression of furin, cleaved Olsa-RVRR intermediates were formed under the effect of intracellular GSH and furin. Then Olsa-dimer was formed through the condensation reaction between CBT and Cys of the intermediates, which will further self-assemble into bigger nanodrugs by the p-p stack to enhance the retention and action time of nanodrugs, obtaining better chemical exchange saturation transfer (CEST) MRI signal and antitumor effects of Olsa.…”
Section: Improving the Intracellular Retention Of Ahcnsmentioning
confidence: 99%
“…Another approach is to incorporate molecular imaging with therapeutic agents to conduct diagnosis and therapy at the same time. The conjugation of drugs with imaging agents provides rich opportunities to develop theranostics (Yuan et al, 2019[ 110 ]) that improve imaging process and drug efficacy (Zhang et al, 2018[ 111 ]; Ji et al, 2018[ 40 ]).…”
Section: Applications Of Biomaterials Based On Noncovalent Interactiomentioning
confidence: 99%
“…[2,3] Applications of this chemistry include site-selective labeling of biomolecules, [2,[4][5][6] and in situ assembly of nanostructures for molecular imaging in vitro and in vivo. [7][8][9][10][11] Asimple three-step mechanism has been proposed for the reaction of CBT with aminothiols ( Figure 1a): 1) the thiolate attacks the nitrile carbon to form at hioimidate;2 )intramolecular attack of the terminal amine at the imino-carbon generates at etrahedral intermediate;3 )deamination of the tetrahedral species releases ammonia and at hiazoline as the final products. [5] However,further detail is lacking.While the addition of monothiols to CBT is generally reversible, [2] irreversible formation of at hioimidate has been reported on the internal cysteine residues within abespoke peptide tag.…”
Section: Introductionmentioning
confidence: 99%